Pengaruh Lamanya Pengadukan Pasta Beton Terhadap Nilai Slump Dan Kuat Tekan (Studi Kasus Pada Beton Normal f’c 24 MPa) - Alif Candra Ghofar Wardana MP; Arminsyah Gumay; Devi Oktarina (Journal of Research in Social Science and Humanities, 2024)
Normal concrete is concrete that uses natural aggregates that are broken or unbroken and does not use additives. In the field of concrete mixing, there are those who use machines and conventionally.  This research is to study the slump value of stirring time and the relationship between slump value and compressive strength of concrete. This research includes a type of experimental research, because it is trying to find new things that can be utilised in the research results. With cylindrical test objects measuring 15 × 30 cm according to SNI testing standards. The research was conducted with 5 variable stirring times, namely, ½ minute, 1, 1 ½, 2, and 2 ½ minutes. As well as the plan compressive strength for the plan age of 14, and 28 days, namely, f'c 24 Mpa. Using a plan slump of 10±2 cm. From the results of this study, the effect of the length of time stirring the concrete paste can make the concrete slump value high. The concrete is difficult to work with, which can be influenced by the cement water factor, aggregate size, aggregate absorption of water, and mixing time. The high slump value is followed by a decreased compressive strength value of the concrete. So that fresh concrete experiences an increase in the levelling value. Therefore, high slump values can affect the quality of concrete.